2018
DOI: 10.1371/journal.pone.0197068
|View full text |Cite
|
Sign up to set email alerts
|

Urinary shedding of pathogenic Leptospira in stray dogs and cats, Algiers: A prospective study

Abstract: BackgroundLeptospirosis is an important worldwide zoonosis. This disease is caused by pathogenic species of the genus Leptospira which are maintained in the environment via chronic renal infection of carrier animals which can be asymptomatic excretors of the organisms in their urines and become a source of infection for humans and other hosts. The prevalence of animal leptospirosis in Algiers, Algeria, is unknown.Methodology/principal findingsReal-time PCR and standard PCR and sequencing were used to detect pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 52 publications
0
23
0
1
Order By: Relevance
“…These data show that although similar species could be isolated from human and rodents, they are genetically different. Furthermore, Leptospira could be shed by other mammals like dogs, bats, livestock; hence, the reservoirs discovery deserves further research [61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…These data show that although similar species could be isolated from human and rodents, they are genetically different. Furthermore, Leptospira could be shed by other mammals like dogs, bats, livestock; hence, the reservoirs discovery deserves further research [61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown prevalence to be 8.2% (USA) [26], 7.05% (Ireland) [27], 14.2% (Brazil) [28], 3.7% (Columbia) [29], 4.8% (Algeria) [30], and 7.6% (New Caledonia) [31]. Classically, L. interrogans serovars, especially Canicola have been associated with asymptomatic renal carriage in dogs [32].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in different geographical areas have demonstrated that cats have contact with Leptospira since they develop specific antibodies ranging from 4% to 33.3%, with no clear association to clinical disease [13][14][15][16][17]. Urinary shedding of Leptospira DNA has also been documented in cats, with a prevalence ranging up to 67.8% depending on various factors including the geographical area, the presence in the area of farm animals infected with leptospires, and prey habits [7,14,15,[18][19][20][21]. Furthermore, a recent study investigated the ability of cats to excrete viable bacteria through urine (p. 227, [19]), suggesting the possibility that cats can spread the bacteria by urine and infect humans.…”
Section: Introductionmentioning
confidence: 99%